Three Phase Motor Centrifugal Machines Speed Control Using Pid Fuzzy Method - Trio Yus Peristiaferi; Rusdhianto Effendie; Josaphat Pramudijanto (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2015)
Induction motor speed settings are still done manually by changing the position of the shaft or the size of the puli engine centrifugal. This method resulted in an arrangement with the speed of the motor will be difficult to control as expected. Inappropriate speed settings can also lead to less sugar production results. It is therefore necessary to maintain the control method of motor speed when load is added while experiencing the process of starting, spinning and breaking. The controller that is used is the PID Fuzzy. In a using simulation and implementation of using controller PID Fuzzy having the averages error when processing starting, spinning and breaking a dising about 0.51 % and about 1.06 %. So this final project hoped can help increase the efficiency of the centrifugal on sugar factory machine.